Risk Factors and Status of Unplanned Readmission of Neonates within Thirty Days of Discharge from NICU at Tertiary Care Hospital of Low Resource Country - Hussain, Ehtisham; Ahmed, Naseem; Ali , Irfan; Iqbal, Javaid; Ahmed, Faraz (Indus Journal of Bioscience Research, 2025)
Background: 12% out of all neonates born alive, require admission to health care facility mainly NICU (4). Neonate that requires readmissions to NICU poses a universal health concern, with frequency as much as 10.1% outside the USA, creating load on health care facilities and parents. Objective: To investigate the risk factors associated with unplanned readmissions of newborns after discharge from the Neonatal Intensive Care Unit (NICU). Methods: A total of 572 neonates who were readmitted to the NICU throughout the study period were also included in this retrospective observational analysis. Data on these readmitted neonates, including gestational age, birth weight, diagnosis, and other factors, were retrieved and evaluated. The chi-square test was applied to see whether there was a relationship between problems and hospital status and newborn demographics. To calculate adjusted odds ratios (ORs) and their 95% confidence intervals (CI), the logistic regression technique using univariate and multivariate data was applied. Result: Out Of 572 study participants, 317(55.4) were male and 255(44.6) were female. The median age of the sample was 1 day (inter-quartile range [IQR]: 0-5 days) with their median length of the NICU stay was 3.00 (2.00 -5.00) days. 78 percent of participants were in born and 22 percent were out born. Most of the newborns during this study were admitted only once (n=496,86.7%) in comparison readmission status was (n=76,13.3%). Among these participants 45 percent were normal birth weight,39 percent were LBW, 10percent ere VLBW and around 6 percent were ELBW. Univariate logistic regression showed that younger age (OR: 1.07, 95% CI: 1.05-1.09) patients who had lesser length of NICU stay were at increased risk of readmission (OR: 0.73, 95% CI: 0.62-0.87). Newborns with very low and low birth weight were had increased odds of NICU readmission in contrast to those whose weight is normal (OR: 4.03, 95% CI: 1.92-8.44, (OR: 2.22, 95% CI: 1.25-3.92). Conclusion: Newborns discharged from NICU are at high risk of readmission, especially in settings with weak community care like Pakistan. Strengthening discharge protocols, caregiver education, and post-discharge follow-ups can reduce readmissions and improve outcomes.